2004
DOI: 10.1093/gerona/59.5.m494
|View full text |Cite
|
Sign up to set email alerts
|

Young and Older Adults Exhibit Proactive and Reactive Adaptations to Repeated Slip Exposure

Abstract: Young and older adults rapidly learned to avoid falling through similar proactive and reactive adaptations that persisted in the short term. Both proactive and reactive adaptations should be targeted in interventions to reduce older adult fall incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
108
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 32 publications
12
108
0
1
Order By: Relevance
“…In terms of practical application of these research findings, previous research has suggested that older adults can benefit from training sessions to avoid falling from a trip 29 or slip 30 . In young adults, trip training resulted in adjustments to the COM position and velocity both proactively and reactively 18 .…”
Section: Discussionmentioning
confidence: 83%
“…In terms of practical application of these research findings, previous research has suggested that older adults can benefit from training sessions to avoid falling from a trip 29 or slip 30 . In young adults, trip training resulted in adjustments to the COM position and velocity both proactively and reactively 18 .…”
Section: Discussionmentioning
confidence: 83%
“…walking or transferring from standing to sitting), and rarely occur during quiet standing 1, 54, 55. Therefore, perturbations should be applied during tasks, such as walking,33, 34 weight shifting39, 56 and rising from a chair 57. Falls can also occur in varied environmental circumstances that pose sensory and mechanical challenges to balance control (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…in the dark/dim light or in the presence of obstacles that impede stepping), and can occur when the individual is distracted. Therefore, PBT programs should consider adding sensory, environmental and cognitive challenges during training to help to promote generalizability of improved reactive balance control to realistic situations 39, 57…”
Section: Resultsmentioning
confidence: 99%
“…In this research, we investigated only muscle responses to clarify ways of adaptation. However, there is the possibility that elderly subjects can adapt by feedforward control to compensate for repeated perturbations-for example, changing the center of mass (COM) location and the movement of upper limbs, as has been shown in several reports [9][10][11][18][19][20] . In addition, we think that change of head movement occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy older adults appeared fully capable of learning to recover better from, or adjusting to, repeated exposures to perturbations during a sit-to-stand task [9][10][11] . Smith et al 12) examined whether a difference exists between muscle responses of older fallers and those of nonfallers during repeated dorsi-flexion perturbations to standing.…”
Section: Introductionmentioning
confidence: 99%